Characterization of the necrotrophic effector ToxA in Kansas fungal leaf spot pathogen populations - Mangel, Dylan Jay Lou (Kansas State University, 2022)
The Kansas fungal necrotrophic wheat leaf spot complex includes the pathogens Bipolaris sorokiniana, Pyrenophora tritici-repentis, and Parastagonospora nodorum. While all of these pathogens utilize multiple pathogenicity factors, in the last 20 years, all three pathogens were discovered to contain a highly conserved copy of the necrotrophic effector (NE) gene, ToxA. Evidence indicates that ToxA was likely transferred between the species through an interspecific gene-transfer event. This gene enables pathogenesis in susceptible hosts through an inverse gene-for-gene interaction with the wheat susceptibility gene, Tsn1. The primary research objectives of this study are to characterize the distribution and diversity of ToxA in the Kansas leaf spot pathogen population, and to determine the frequency of the genes ToxA, ToxB, and ToxC in the P. tritici-repentis population. A survey of Kansas cereals was conducted to collect isolates of leaf spot pathogens. Isolates of all three pathogens were molecularly characterized for presence of ToxA and their haplotype diversity was evaluated through comparison of ToxA sequences. Isolates of P. tritici-repentis were phenotypically screened against a wheat differential set, and molecularly characterized for presence of the genes ToxA, and ToxB. Results show that the NE gene ToxA was represented in 87% and 100% of P. tritici-repentis and P. nodorum isolates respectively, while only being represented in 44% of B. sorokiniana isolates. Additional evaluation of the P. tritici-repentis population showed that in addition to ToxA, only ToxC was common in the collected isolates. Characterization of the haplotype diversity in the three populations showed that the characterized isolates contain limited genetic diversity in all three backgrounds, but the most limited diversity is in the P. tritici-repentis population. The result that ToxA has now been found in three Kansas pathogen populations highlights the importance of ToxA and its susceptibility factor (Tsn1) in wheat. Knowledge about the rates of ToxA in these populations will help pathologists in making management recommendations and will help breeders make selection decisions. Now that a baseline for ToxA has been established in the B. sorokiniana population in Kansas, future surveillance will be required to monitor for an increase of the NE gene. As ToxA likely increases pathogen fitness, selection in the population could potentially lead to a future in which B. sorokiniana is a more economically important pathogen.
Keywords: Tan spot; Necrotrophic effector; Pyrenophora tritici-repentis; Bipolaris sorokiniana; Parastagonospora nodorum